0271 Adverse effects on specific markers of cardiovascular risk among workers exposed to multi-walled carbon nanotubes. (21st August 2017) - Kuijpers, Eelco; Pronk, Anjoeka; Kleemann, Robert; Vlaanderen, Jelle; Rothman, Nathaniel; Silverman, Debra; Lan, Qing; Hoet, Peter; Godderis, Lode; Vermeulen, Roel
Abstract : The increase in production of Multi-Walled Carbon Nanotubes (MWCNTs) goes along with growing concerns about health risks. Few, rather small, studies have reported biological effects of MWCNTs in humans including increased concentrations of cardiovascular markers fibrinogen, ICAM1 and IL-6, but findings are largely inconsistent. The objective of this study was to assess the association between occupational exposure to MWCNTs and biomarkers of cardiovascular risk. A cross-sectional biomarker study was performed among workers of a company commercially producing flexible MWCNTs and a matched unexposed population. 12 cardiovascular markers were measured in participants' blood (phase 1). In a sub-population these measures were repeated after 5 months (phase 2). We analysed associations between MWCNT exposure and biomarkers of cardiovascular risk, corrected for age, BMI, sex and smoking. 22 exposed and 42 unexposed workers were included in phase 1 and a subgroup of 13 exposed workers and 6 unexposed workers in phase 2 of the study. Both in phase 1 and phase 2 we observed an upward trend in the concentration of endothelial damage marker ICAM-1, with increasing exposure to MWCNTs. This finding is supported by significantly elevated monocyte counts among the same workers. No significant associations were found between exposure to MWCNTs and the other cardiovascular markers tPA, Fibrinogen, VCAM-1, IL-6, E selectin, TNF-α and D-Dimer. The results of the present study should be viewed as explorative and requires confirmation in larger studies. Our results for ICAM-1 point towards a potential for endothelial damage due to exposure to MWCNT.